2015
DOI: 10.1177/2165079915607494
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Measures Aimed at Noise Reduction in an Intensive Care Unit

Abstract: Noise is a significant problem for both hospitalized patients and health care workers. This study aimed to determine the effectiveness of noise reduction strategies in an intensive care unit. Noise was measured in two phases. In the first phase, the unit's present level of noise was established over 3 weeks between January 1, 2012, and February 1, 2012. During the month following initial measurements, noise reduction interventions, including staff education and physical space arrangement, were initiated, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 43 publications
(51 reference statements)
2
7
0
4
Order By: Relevance
“…Reported interventions include staff education about the importance of sleep and the use of noise monitoring equipment to alert staff to increases in noise volume [ 35 ]. Kol et al demonstrated a significant reduction in environmental noise levels in an intensive care environment after the introduction of staff education and a rearrangement of the ward environment (67.6 dB[A] pre versus 56 dB[A] post, p < 0.05) [ 38 ]. In contrast, Nannapaneni et al reported that a multipronged noise intervention inclusive of education and noise monitoring had a minimal effect on ambient noise levels, but did result in a reduction in the number of noise ascensions [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Reported interventions include staff education about the importance of sleep and the use of noise monitoring equipment to alert staff to increases in noise volume [ 35 ]. Kol et al demonstrated a significant reduction in environmental noise levels in an intensive care environment after the introduction of staff education and a rearrangement of the ward environment (67.6 dB[A] pre versus 56 dB[A] post, p < 0.05) [ 38 ]. In contrast, Nannapaneni et al reported that a multipronged noise intervention inclusive of education and noise monitoring had a minimal effect on ambient noise levels, but did result in a reduction in the number of noise ascensions [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Behavior-based sound reduction studies comparing staff education, education with sound monitoring, and education with environmental modifications had mixed results, with no improvement in sound levels in some studies 128 and a reduction in others (►Table 1). 80,129 Notably, sound reduction interventions did not evaluate sustainability, and decibel levels commonly remained above recommended limits. 80,130 While sound masking with white noise has been demonstrated to improve sleep quality, [105][106][107] sound blocking via earplugs has received particular attention due to recent research suggesting improved sleep perception, satisfaction, and delirium in ICU patients wearing earplugs.…”
Section: Sound In the Icumentioning
confidence: 99%
“…Z výsledků zahraničních studií se dá odhadovat podobné zařazení pracovníků do rizikových a nerizikových kategorií s tím, že jen 2,2 % zdravotnických a sociálních pracovníků bylo vystaveno rizikovým hladinám hluku (8). Kol hodnotil hlukové podmínky na jednotce intenzivní péče před a po zavedení strategií na redukci hluku a z jeho výsledků vyplynulo, že došlo ke snížení průměrné hladiny hluku o téměř 12 dB (17).…”
Section: Diskuzeunclassified